O funcionamento discursivo dos textos de contracapa da “Coleção Vampiro” - Jorge, Noémia (Revista da Associação Portuguesa de Linguística, 2021)
The present article presents a comprehensive study on the discursive functioning of the detective novels back cover texts of the Coleção Vampiro (CV), published every month in Portugal between 1947 and 2008. From a descriptive and linguistic perspective which assumes the discourse types (Bronckart 1997, 2008) as a category of analysis, they are analysed the back cover texts of 104 volumes from the CV (14,6% of the collection), adopting a mixed methodology which integrates both quantitative and qualitative methods. It is concluded that, in the first part of the collection, the book cover texts present a predominantly expositive dimension as well as a strong implication of both the speaker and the receiver, which contributes to the dissemination and popularization of the detective novel genre. In the second part, the texts present a predominantly narrative dimension and they are marked by the erasure of the speaker and the receiver, corresponding almost entirely to the synopsis of the detective novel in question